Μελέτη του φαινομένου της αστικής θερμικής νησίδας - Χρυσάνθου, Χριστίνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The aim of the present bachelor’s thesis is the study of the so-called phenomenon of Urban Heat Island (UHI), the characteristics and the factors that cause the development and the intensity of the phenomenon and ways to mitigate its effects. Studies associated with the UHI in the Mediterranean are described in depth in this study with focus on how the intensity of the UHI was measured, in which time the phenomenon develops, the season that the phenomenon is at its maximum, as well as the effect that urban construction materials have on the development of the UHI. In this study, temperature-humidity sensors and thermal-camera were used in order to study the phenomenon. The sensors were placed in several locations with different altitudes in order to get measurements from different sites (e.g. measurements from urban and suburban areas). The thermal-camera was used with the purpose of examining which materials contribute to the creation and the development of UHI. The experimental part of the study shows the existence of the UHI and the results indicate that the creation and the development of the phenomenon depend on several materials and on the location in which the sensors were placed (e.g. different surfaces). At the end, suggestions of which materials must be used in order to reduce the phenomenon are stated.
Keywords: Urban heat island (UHI); Temperature-humidity sensors; Thermal-camera; Αστική θερμική νησίδα; Aισθητήρες θερμοκρασίας - υγρασίας; Θερμοκάμερα